1995
DOI: 10.1101/gad.9.15.1933
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome positioning on the MMTV LTR results from the frequency-biased occupancy of multiple frames.

Abstract: The translational positions of nucleosomes in the promoter region of the mouse mammary tumor virus (MMTV) were defined at high resolution. Nucleosome boundaries were determined in primer extension assays using full-length single-stranded mononucleosomal DNA prepared from cells treated with formaldehyde, a reversible protein-DNA cross-linking agent. Multiple boundaries were observed in both the nucleosome A (Nuc-A) and Nuc-B region of the promoter, indicating multiple nucleosome translational frames. The differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
124
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(134 citation statements)
references
References 62 publications
(97 reference statements)
9
124
1
Order By: Relevance
“…Roberts et al (38) observed clear 10-bp periodicities for an in vitro reconstitute that contained five different core positions, demonstrating the difficulty of using this criterion for determination of high resolution positions. Similar data from several other systems (summarized in Fragoso et al (33)) is also consistent with multiply positioned cores within families. Thus, the preponderance of evidence at this time would argue that even in highly organized and reproducible systems, such as the MMTV LTR, considerable complexity exists in nucleosome positioning.…”
Section: The Mmtv Modelsupporting
confidence: 77%
See 2 more Smart Citations
“…Roberts et al (38) observed clear 10-bp periodicities for an in vitro reconstitute that contained five different core positions, demonstrating the difficulty of using this criterion for determination of high resolution positions. Similar data from several other systems (summarized in Fragoso et al (33)) is also consistent with multiply positioned cores within families. Thus, the preponderance of evidence at this time would argue that even in highly organized and reproducible systems, such as the MMTV LTR, considerable complexity exists in nucleosome positioning.…”
Section: The Mmtv Modelsupporting
confidence: 77%
“…This structure was originally characterized as a periodic array of micrococcal nuclease and methyldiumpropyl-EDTA-Fe(II) cleavage-sensitive internucleosomal linker regions (35). More recently, using an in vivo cross-linking procedure for determining nucleosome core positions, Fragoso et al (33,37) concluded that the periodic array does not represent precisely positioned nucleosomes but rather consists of a series of nucleosome families (Fig. 1A, A-F) (33).…”
Section: The Mmtv Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMTV-LTR has six well defined positioned nucleosome families, designated nucleosomes (Nuc) A-F. NucA overlaps the TATA region and the transcription start site, and NucF is the farthest 5Ј to the transcription start site (Ϫ1 kilobase) (Fig. 1A) (22,23). Four GR binding sites or hormone response elements (HREs) are located in the NucB region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the superantigen sequence is hypervariable and this affects sequences across nucB (Brandt-Carlson et al 1993), so care is needed when comparing results from different isolates and this may have led to different nucleosome mapping assignments (Piña et al 1990;Archer et al 1991;Fragoso et al 1995;Flaus and Richmond 1998).…”
Section: Mmtv Ltr Nucleosomes a And Bmentioning
confidence: 99%